Outdor Learning Sebagai Penerapan P5 Kurikulum Merdeka Pada Pembelajaran Sejarah - Jauhar*, Sitti Jauhar; Dewi Riang Tati, Andi Dewi Riang Tati; Ilham, Muhammad Ilham (JIM: Jurnal Ilmiah Mahasiswa Pendidikan Sejarah, 2024)
This research aims to find out how learning outside the classroom as an implementation of the P5 Independent Curriculum at SMAN 22 Gowa can provide learning motivation and improve student learning outcomes. Learning outside the classroom is an effort to direct students to carry out activities that can lead them to observe the surrounding environment, in accordance with the material being taught. So that education outside the classroom is more focused on experience and environmental education which greatly influences students' intelligence. In line with the Merdeka Curriculum through P5 (Projek Penguatan Profil Pelajar Pancasila). The techniques for collecting data using observation, interviews and documentation that are the samples in this research are: Teachers, students as the main source of information for researchers.